(untitled) (Bioscience Journal, 2019)
The objective of this work was to evaluate the profitability of sweet potato cultivars, harvested at different ages and cultivated in different periods (rainy and dry) in the municipality of Mossoró, semi-arid region of Rio Grande do Norte. The experimental design was a randomized complete block design with four replications and treatments arranged in split plots scheme. The plots were composed of three sweet potato cultivars (ESAM 1, Paraná and Mother of Family) and the subplots for five harvest ages (90 , 105, 120, 135 and 150 days after transplanting - DAT). Productivity of commercial roots and production costs was evaluated, as well as the economic indicators: gross income, net income, rate of return and profit margin. Independently of the growing periods, the productivity of commercial roots increased with the later harvest of the crop and differentiated the cultivars. Production costs averaged R 6,087.97 ha-1 in the rainy season and R 6,181.42 ha-1 in the dry period. Labor expenditures were the most impacting of total expenditures. The cultivars ESAM 1 and Paraná presented higher productivities of commercial roots and profitability when cultivated in the rainy season, while Paraná cultivar was superior to the other cultivars in the crop in the dry season. In both growing periods, the harvest age of 150 DAT promoted higher productivities of commercial roots and profitability to sweet potato production.